Towards the selection of critical indicators in educational centers - Mª Antonia Casanova (ADIDE Federación, 2007)
Usually implicitly -but sometimes even explicitly-, assessment determines the way in which schools are run, as well as the teaching process and the learning process. It conditions everyday tasks at schools and discriminates between valuable and worthless items in Education. Society appreciates some elements or others, depending on the assessment they obtain, and does not know -or does not want to know, actually- about un-assessed features. Therefore, it is of vital importance to select the most suitable set of indicators, the ones that will show the main aspects of school management. The mere selection and expression of the critical indicators for a certain school would provoke a crisis at school, and would mark the beginning of a necessary course-correction in the school management, towards some qualitative improvement of its offer to students.